Investigating teaching presence in online discussion forums / Aida Mustapha - Mustapha, Aida (2005)
The discussion forum is a vital component of online courses. Studies by Berge (1997), Gunawardena et al. (1997) and Garrison et al. (2000, 2001) showed that these asyrtchronous forums have the potential to promote critical thinking, meaningful problem solving, and knowledge construction. This case study investigated how four E-PJJ instructors at UiTM Terengganu Kampus Dungun used their online discussion forums to facilitate online students in their studies. In this study, the researcher looked into the aspects of teaching presence based on the instructors posted messages and compared them with Garrison & Anderson's (2003) teaching presence indicators. The study discovered the discussion forums were under utilized and they were used mainly for class management and assessments handling instead of academic discussions on course contents. This was mainly because online discussions were not .part of the students' assessments. It was also found that non-language forums were more active compared to language forums.